2011
DOI: 10.1111/j.1574-695x.2011.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Chlamydia trachomatis directly from urogenital and conjunctiva samples using an ompA gene pyrosequencing-based assay

Abstract: The aim of the present study was to develop and validate a multitarget pyrosequencing-based protocol for basic Chlamydia trachomatis genotyping directly from clinical samples and to characterize the distribution of genotypes among Slovenian sexually active population. The newly developed combination of assays that targets the variable domains VD-I and VD-IV of the C. trachomatis ompA gene, was optimized and validated with 11 reference C. trachomatis strains and by comparison to complete ompA conventional seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Overall, this crossroad location between Europe and Asia dictates a multi-ethnic population and high migration area that may explain the relatively high prevalence of chlamydial infection (72.1 per 100,000 people) [ 31 ]. This specific geographic setting provided an opportunity to identify the pattern of representative genovars and compare it with the worldwide distribution of most prevalent strains, such as D, E, F and G together with three other genovars, H, J and K, typical for chlamydial genital infection [ 5 , 7 , 12 20 , 23 , 32 34 ]. In contrast to previous surveys from other countries, which revealed that the heterosexual population was infected with the dominating genovars D, E, G, or E alone, or E followed by F [ 7 , 15 , 33 ], the Saratov Region had a strikingly low representation of the genovar D with the prevalent domination of genovar E followed by G and F ( Fig 1A ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, this crossroad location between Europe and Asia dictates a multi-ethnic population and high migration area that may explain the relatively high prevalence of chlamydial infection (72.1 per 100,000 people) [ 31 ]. This specific geographic setting provided an opportunity to identify the pattern of representative genovars and compare it with the worldwide distribution of most prevalent strains, such as D, E, F and G together with three other genovars, H, J and K, typical for chlamydial genital infection [ 5 , 7 , 12 20 , 23 , 32 34 ]. In contrast to previous surveys from other countries, which revealed that the heterosexual population was infected with the dominating genovars D, E, G, or E alone, or E followed by F [ 7 , 15 , 33 ], the Saratov Region had a strikingly low representation of the genovar D with the prevalent domination of genovar E followed by G and F ( Fig 1A ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar CT genovar distribution has been recently observed in Greece in male patients with urethritis [ 14 ]. Likewise, it was shown recently that in Slovenia and Kharkiv Region (Ukraine) that genovars E, G and F were the most prevalent, although in a different proportion [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prevalent serovars were E (30.2 %) and F (28.3 %), and this trend is in accordance with the findings of other genotyping studies worldwide. Many studies examining the serovar distribution of C. trachomatis in genital samples of different cohorts using genotyping methods have shown that the most frequently observed serovars are E and F (Lysén et al, 2004;Gao et al, 2007;Lima et al, 2007;Kese et al, 2011). The similar distribution of ocular and genital serovars supports the theory that adult chlamydial conjunctivitis infections have a genital source, as has been suggested previously by several studies, and can occur during autoinoculation or transmission from the partner's infected genital secretions (Stenberg & Mårdh, 1991;Garland et al, 1995;Postema et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, determination of the C. trachomatis serovars by molecular typing methods provides epidemiological information about the incidence and prevalence of the actual serovars of the isolated conjunctival C. trachomatis strains. However, there are limited data available about the distribution of ocular C. trachomatis serovars in adult populations (Garland et al, 1995;Isobe et al, 1996;Kese et al, 2011). The aims of the present study were: (i) to define the prevalence of C. trachomatis by PCR in eye samples of individuals with conjunctivitis; (ii) to identify retrospectively the different C. trachomatis serovars by genotyping; and (iii) to analyse the relationship between demographics (age and gender) and C. trachomatis infection in patients with conjunctivitis.…”
Section: Introductionmentioning
confidence: 99%